Retroperitoneal Leiomyoma (Journal of Surgical Sciences, 2019)
Leiomyoma is a common benign condition for which many hysterectomies are performed everyyear. Leiomyomas found retroperitoneally are a rare entity, especially primary. We report herea case of 44-year-old, para 5+0 who presented with mass in the abdomen and lower abdominalpain. CT- scan shows a huge retroperitoneal soft tissue mass. The mass was removedcompletely. Histopathological findings were consistent with leiomyoma. Retroperitonealleiomyoma is a rare neoplasm and treatment is surgical removal.Journal of Surgical Sciences (2016) Vol. 20 (1) : 26-28